Chronology of Registrogenesis in Khmer: Analyses of Poetry and Inscriptions - Maspong, Sireemas (Journal of the Southeast Asian Linguistics Society, 2024)
This study examines the phonological changes in Khmer, focusing on the loss of onset voicing, the emergence of register contrast, and the development of a bifurcated vowel system. By analyzing rhyme pairs from Khmer poetry (16th-19th centuries) and spelling variations in Khmer inscriptions (late 7th-mid-18th centuries), I propose a chronology of these changes. The results indicate that vowel mergers resulting from vowel bifurcation in the rhyme pairs appeared from the 17th century onwards. Additionally, spelling variations reflecting the loss of onset voicing and the vowel mergers were observed in inscriptions dating back to the late 16th century. These findings align with previous research, suggesting that both the loss of onset voicing and the vowel bifurcation occurred in the late 16th century. However, the relative chronology of these changes remains uncertain since evidence for both changes emerges around the same time.